Comparative study of the permanent dentition among 12- year-old children in the Lublin Region - Bachanek, Teresa; Klichowska-Palonka, Małgorzata; Wolańska, Ewa; Orłowski, Mirosław (Polish Journal of Public Health, 2009)
Aim. The objective of the study was the analysis of dental caries tendency over a 20-year-period among 12-year-old children living in rural areas and small towns in the Lublin Region in the years 1987, 1997 and 2007.Material and methods. Dental examination was performed according to the WHO guidelines for epidemiological studies. A total number of 421 children were examined, including 238 rural inhabitants and 183 living in small towns. The state of mineralized tissues of the teeth was evaluated based on the intensity and frequency of dental carries.Results and conclusion. During the period of 20 years the epidemiological situation concerning carious disease in the population examined, described by means of the values of selected indices, showed improvement only in the group of rural boys. It seems justifiable to analyze the selected indices in the Lublin Region once again in order to implement more effective prophylactic-treatment methods counteracting the development of carious disease.